FAMILY CAREGIVERS EXPERIENCE OF CARING FOR A LOVED ONE WITH DELIRIUM: A SYSTEMATIC REVIEW. (11th November 2018) - Shrestha, P; Fick, D
Abstract: Background: Delirium is a common neuropsychiatric illness among hospitalized older adults that result in poor outcomes including increased mortality and progression to dementia. However, very little is known about the experience of the family caregiver of persons with delirium. The purpose of this paper is to advance understanding of the experiences of family caregivers caring for an older adult with delirium across care settings in order to target areas for improving practice and future research. Methods: A systematic literature review was conducted in PubMed, CINAHL, PsycINFO, Trip, and Cochrane databases per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria and articles were graded for evidence quality. Both qualitative and quantitative data were included. Results: From the total of 2, 054 articles identified, after systematic elimination, eleven articles were selected as eligible for review. Studies reviewed reported themes that family members were shocked to view the unexpected, rapid, and unpredictable changes in the older adult and were concerned about the burden of care. The studies also reported that caregivers had a sense of personal loss (no personal and social life) and loss of the loved one (acts as a stranger). Conclusions & Implications: Families caring for older adults reported it as overwhelming, isolating, and lacked education about delirium. However, willingness to be involved in the care being provided was evident in this review. Practice and research implications and gaps in knowledge will be discussed.